"دور مصداقية المواقع الألكترونية في تحسين الأداء المالي "دراسة إستطلاعية في المصارف التجارية في السليمانية - احمد, رزكار علي; عبدالرحمن, به روه ر ابراهيم (Sulaimani Journal for Humanities, 2021)
This study aimed to measure the reliability of electronic accounting information systems in banks, by identifying the extent to which they provide the principles of reliability of information systems, developed by: The American Institute of Certified Public Accountants and the Canadian Institute of Certified Public Accountants, and by using appropriate methods in collecting and analyzing data, while enhancing the study models with variables Control. The study found that banking information systems are in statistical terms based on the principles of reliability of information systems, but with varying proportions, and the study also found that there is a statistically significant effect of providing accounting information systems for reliability principles in financial, operational, and equity performance indicators for banks, but it did not find a significant difference. Interbank statistics regarding the provision of accounting information systems for reliability principles Based on these results, the study indicated a set of recommendations, the most important of which were: Inviting banks to perform the task of monitoring the reliability of accounting information systems, to perform confidence assurance services in electronic systems, and the necessity of adopting the bodies regulating the work of banks and relying on the reliability system and adopting it as one of the conditions for practicing the profession, which will be reflected. Positively for the work of those banks, and for the organization of the banking sector